Quality of life 3 and 12 months following acute pulmonary embolism: analysis from a prospective multicenter cohort study - Valerio, Luca; Barco, Stefano; Jankowski, Marius; Rosenkranz, Stephan; Lankeit, Mareike; Held, Matthias; Gerhardt, Felix; Bruch, Leonhard; Ewert, Ralf; Faehling, Martin; Freise, Julia; Ghofrani, Hossein-Ardeschir; et al. (Chest, 2021)
Background - Few data are available on the long-term course and predictors of quality of life (QoL) following acute pulmonary embolism (PE). - Research Question - What are the kinetics and determinants of disease-specific and generic health-related QoL 3 and 12 months following an acute PE? - Study Design and Methods - The Follow-up after Acute Pulmonary Embolism (FOCUS) study prospectively followed up consecutive adult patients with objectively diagnosed PE. Patients were considered for study who completed the Pulmonary Embolism Quality of Life (PEmb-QoL) questionnaire at predefined visits 3 and 12 months following PE. The course of disease-specific QoL as assessed using the PEmb-QoL and the impact of baseline characteristics using multivariable mixed effects linear regression were studied; also assessed was the course of generic QoL as evaluated by using the EuroQoL Group 5-Dimension 5-Level utility index and the EuroQoL Visual Analog Scale. - Results - In 620 patients (44% women; median age, 62 years), overall disease-specific QoL improved from 3 to 12 months, with a decrease in the median PEmb-QoL score from 19.4% to 13.0% and a mean individual change of -4.3% (95% CI, -3.2 to -5.5). Female sex, cardiopulmonary disease, and higher BMI were associated with worse QoL at both 3 and 12 months. Over time, the association with BMI became weaker, whereas older age and previous VTE were associated with worsening QoL. Generic QoL also improved: the mean ± SD EuroQoL Group 5-Dimension 5-Level utility index increased from 0.85 ± 0.22 to 0.87 ± 0.20 and the visual analog scale from 72.9 ± 18.8 to 74.4 ± 19.1. - Interpretation - In a large cohort of survivors of acute PE, the change of QoL was quantified between months 3 and 12 following diagnosis, and factors independently associated with lower QoL and slower recovery of QoL were identified. This information may facilitate the planning and interpretation of clinical trials assessing QoL and help guide patient management. - Clinical Trial Registration - German Clinical Trials Registry (Deutsches Register Klinischer Studien: www.drks.de); No.: DRKS00005939.